Delisting and its relation to earnings management practices (Research, Society and Development, 2021)
This study intends to explain two important and related topics for the national capital market: earnings management and delisting. This is due to an attempt to find standards that explain the importance of the quality of accounting information and to assist managers and stakeholders in making market decisions. This article aims to achieve its goal when relating results management and delisting. For this, a regression was first made based on the model of Kang e Sivaramakrishnan (1995), to measure discretionary accruals as a proxy for results management. In significant terms, this article found a relationship between control variables size and indebtedness with the management of results and, consequently, with the quality of accounting information, aligning with the existing literature. However, it was not possible to identify in the studied sample the significance between results management and delisting.